PENGARUH LIQUIDITAS, PROFITABILITAS, LEVERAGE DAN COVERAGE RATIO TERHADAP PERINGKAT OBLIGASI (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI DAN PT. PEFINDO) - Ahmad Ardi Kurniawan (JURNAL EKOBIS DEWANTARA, 2019)
This study aims to determine (1) the effect of liquidity as measured by the current ratio of the bond rating (2) the effect of profitability as measured by return on assets to the bond rating (3) the effect of leverage as measured by the debt to equity ratio of the bond rating (4) the effect of coverage ratio measured by time interested earned on bond ratings. This research uses secondary data. The study population is a banking company listed on the Indonesia Stock Exchange (IDX) and PT Pemeringkat Efek Indonesia (PT Pefindo) in the 2014 to 2018 period of 10 companies. The sampling technique used was purposive sampling technique. Data analysis techniques using binary logistic regression using SPSS 23 analysis tools.